A porous biochar supported nanoscale zero-valent iron material highly efficient for the simultaneous remediation of cadmium and lead contaminated soil - Qian, Wei; Liang, Jing-Yi; Zhang, Wen-Xuan; Huang, Shi-Ting; Diao, Zeng-Hui (Journal of environmental sciences (China), 2022)
•Immobilization of metals by BC-nZVI process was superior to that of BC or nZVI.•Immobilization of Cd or Pb was inhibited with addition of 2,4-dichlorophenol.•Cd and Pb availability decreased, whereas soil pH and organic matter increased.•Stable metals speices such as CdCO3, Cd(OH)2, PbCO3 and Pb(OH)2 were formed.•Mechanism for the simultaneous immobilization of Cd and Pb in soil was proposed. Risk associated with heavy metals in soil has been received widespread attention. In this study, a porous biochar supported nanoscale zero-valent iron (BC-nZVI) was applied to immobilize cadmium (Cd) and lead (Pb) in clayey soil. Experiment results indicated that the immobilization of Cd or Pb by BC-nZVI process was better than that of BC or nZVI process, and about 80% of heavy metals immobilization was obtained in BC-nZVI process. Addition of BC-nZVI could increase soil pH and organic matter (SOM). Cd or Pb immobilization was inhibited with coexisting organic compound 2,4-dichlorophenol (2,4-DCP), but 2,4-DCP could be removed in a simultaneous manner with Cd or Pb immobilization at low concentration levels. Simultaneous immobilization of Cd and Pb was achieved in BC-nZVI process, and both Cd and Pb availability significantly decreased. Stable Cd species inculding Cd(OH)2, CdCO3 and CdO were formed, whereas stable Pb species such as PbCO3, PbO and Pb(OH)2 were produced with BC-nZVI treatment. Simultaneous immobilization mechanism of Cd and Pb in soil by BC-nZVI was thereby proposed. This study well demonstrates that BC-nZVI has been emerged as a potential technology for the remediation of multiple heavy metals in soil. [Display omitted]